Southern sass and a battered bride - Young, Kate (Mystery writer) (Young, Kate (Mystery writer). Marygene Brown mystery., 2021)
"Marygene Brown always figured she'd marry her childhood sweetheart, Alex Myers, not cater his wedding...Marygene may have to smile through the festivities, but Mama doesn't have to hold her peace--especially since only Marygene can hear her mother's ghost...So when Marygene finds Lucy lying beside the wedding cake, buried in batter, with no pulse...and...the bride's body simply vanishes, it's up to Marygene and her best friend Betsy (cousin to the groom and no fan of the bride) to solve a real-life mystery--with a little help from Mama's sassy spirit"--